LANGUAGE SYSTEM AND ITS STRUCTURAL FEATURES - Akramova K.A (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstact This  study  investigates  the  structure  of  the  English  language,  examining  the phonetic,  morphological,  syntactic,  lexical,  and  semantic  levels  and  their interrelationships. It demonstrates that each level performs specific functions while interacting to ensure clarity, coherence, and expressiveness in communication. The findings  highlight  the  importance  of  understanding  these  patterns  for  language learning, effective communication, and language teaching.